(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
It was found that in acute destructive pancreatitis occur microcirculation system changes, both in the breast tissue, and other organs and systems. [1-2]. One of the most sensitive to hypoxia arising structures is the mucous membrane of the digestive tract. [3]. It is known that erosive lesions of the mucous membrane of the esophagus, stomach, duodenum often occurs in acute pancreatitis, but it is unclear whether there is a relationship between the degree of change in this area and the severity of acute pancreatitis. [4-7].